Students' Analyses toward Grammatical Errors on Social Media's Posts: Case Study in Politeknik Negeri Medan - Orli Binta Tumanggor; Aprilza Aswani; Winda Syafitri (FOSTER: Journal of English Language Teaching, 2021)
Learning a second or foreign language is quite different from acquiring the first language or mother tongue. There are some differences found in different languages including the grammatical pattern. It tends to make the learners have errors in writing or speaking English. This study investigated the students’ analyses toward grammatical error on social media posts. The subject of research are 15 students of Politeknik Negeri Medan majoring computer engineering.There were 20 errors found by students which were further analyzed by using surface taxonomy theory. This study showed that the students’ analyses were dominantly on misformation analysis, followed by omission, addition, and misordering analysis. Misformation is the highest rate of errors found as it actually covers many grammar topics in english such as tenses, participle, verbal sentence, nominal sentence, part of speech, and others as analyzed by students on social media posts. Besides, no students found blends analysis, it might due to their lack of knowledge of blends itself. Key word: Grammatical error, social media, surface taxonomy theory